Livestock in the mountains and highlands of Asia, Africa and South America: An overview of research and Development issues and challenges - Tulachan, P.M.; Partap, T.; Maki-Hokkonen, J.; Mohamed-Saleem, M.A.; Rajbhandari, B (International Centre for Integrated Mountain Development, 2000)
This chapter provides an overview of the main points raised in the papers presented at this workshop. The issues raised are summarised from all three regions under different thematic headings. The major issues include livestock in mountain and highland economies; trends and management strategies in livestock production systems; smallholder dairies and factors affecting their success; natural resource management, environment and sustainability concerns; livestock biodiversity and other produciton resources; gender concerns in livestock management; technological and institutional issues; policy issues for livestock Development; constraints to livestock production systems; and livestock research and Development issues. This summary is followed by working group sessions and recommendations.